Efficacy analysis of hemostatic spray following endoscopic papillectomy: A multicenter comparative study. Issue 11 (4th October 2022) - Lee, Kyong Joo; Lee, Tae Hoon; Cho, Jae Hee; Hyun, Jong Jin; Jang, Sung Ill; Jeong, Seok; Park, Jin‐Seok; Yang, Jae Kook; Lee, Don Haeng; Lee, Dong Ki; Park, Sang Heum
Abstract: Background and Aim: Endoscopic post‐papillectomy bleeding is a serious adverse event with a prevalence ranging from 2% to 45.3%. Conventional hemostatic methods, including diluted epinephrine injection before papillectomy or argon plasma coagulation after papillectomy, did not show a preventive role in reducing immediate or delayed post‐papillectomy bleeding. Therefore, we aimed to assess the efficacy and safety of a hemostatic powder spray for post‐papillectomy bleeding and compare with those of conventional modalities. Methods: Patients who underwent endoscopic papillectomy were enrolled in five tertiary hospitals. The group was divided into hemostatic spray and conventional control groups according to the bleeding control methods. The main outcome measurements were delayed bleeding rate and any adverse events related to the procedures. Results: A total of 40 patients who received a hemostatic spray ( n  = 18) or conventional hemostatic methods ( n  = 22) after endoscopic papillectomy were included. The prevalence of delayed bleeding was not different in the two groups: 27.8% and 36.4% in hemostatic spray and conventional control groups ( P  = 0.564), respectively. The adverse events such as post‐papillectomy pancreatitis and cholangitis were not different in the two groups. There were no procedure‐related mortalities. Conclusion: Hemostatic spray is technically feasible and safe for the prevention or management of post‐papillectomy bleeding. Hemostatic spray can be one of the options for post‐papillectomy bleeding control methods owing to its convenient use.